Restatement Kelalaian Dalam Malpraktik Medis - Eko Pujiyono (Perspektif Hukum, 2023)
Research on restatement of negligence in medical malpractice aims to address the issue of uncertainty over legal adjudication in determining the unlawful nature of medical negligence. This research is an effort  to create a clear explanation about the prominent concept of criminal law that are more fairly in the law enforcement of the criminal law code on negligence cases. In addition, this research is expected to create a new approach in the development of legal methods that is a system of assessments and legal discourse by universities, practitioners and other health law observers to get a real and fair result. This research  uses a normative approach and based on conceptual category, regulations, and court decisions. These three elements are reviewed together by considering universal legal principles. A verification  of unlawful nature in medical malpractice has different characteristics rather than the ordinary  crimes proof. The sui generis characteristic in health law has an impact on legal constructions toward negligence cases. A Proving negligence in Health Law requires a medico-legal approach. Legal adjudication of cases of negligence in medical practice in Indonesia requires adjustments to the legal doctrines that apply in the science of health law. This legal doctrine has applied as universal doctrin and be a part of studying to find unlawful aspect in criminal acts relating with the field of health care law.